2021
DOI: 10.1177/17411432211012011
|View full text |Cite
|
Sign up to set email alerts
|

Arab scholarship in educational administration, management and leadership: An overview

Abstract: Following in the tradition of systematic reviews of research, this paper reports the findings of an overview of Arab scholarship in educational administration, management and leadership. We first articulated a framework for analysis anchored to a proposed ‘scholarship maturity’ theoretical model then applied it to analyze 20 reviews of Arab scholarship in educational administration, management and leadership. The findings suggest that reviewing Arab scholarship in educational administration, management and lea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 54 publications
0
0
0
Order By: Relevance
“…To make the Khilafah model of educational administration a viable alternative requires a critical mass of scholars with a shared vision and effective means of scholarly communication who dedicate systematic efforts to chart out plans and courses of action. Bibliometric studies that were conducted on Arab scholarship in educational administration (Atari & Essa, 2021;Atari & Outum, 2019) and on educational administration in some Islamic countries (Ahmed, 2020) revealed that there is a limited number of scholarly articles on Islamic-informed educational leadership, no centers for developing knowledge or training practitioners, no academic journals and, above all, no critical mass of specialized scholars. The interest is limited to a few scholars who mostly write theses or do research in sparse time and to a few courses offered in some universities.…”
Section: The Desideratamentioning
confidence: 99%
“…To make the Khilafah model of educational administration a viable alternative requires a critical mass of scholars with a shared vision and effective means of scholarly communication who dedicate systematic efforts to chart out plans and courses of action. Bibliometric studies that were conducted on Arab scholarship in educational administration (Atari & Essa, 2021;Atari & Outum, 2019) and on educational administration in some Islamic countries (Ahmed, 2020) revealed that there is a limited number of scholarly articles on Islamic-informed educational leadership, no centers for developing knowledge or training practitioners, no academic journals and, above all, no critical mass of specialized scholars. The interest is limited to a few scholars who mostly write theses or do research in sparse time and to a few courses offered in some universities.…”
Section: The Desideratamentioning
confidence: 99%
“…With the advancement of the second classroom, our learning style has changed accordingly [8]. The informationization of social life and the globalization of the economy has made the importance of student education management increasingly prominent [9]. Facing the requirements of the new era, how to implement the fundamental task of moral education management of students in the second course, from the actual needs of local universities and students' growth, accurately grasp the characteristics and growth dynamics of students, and innovate the working mechanism based on student education management is a systematic project that needs comprehensive reform from the concept, a working mechanism to the way of realization [10].…”
Section: Introductionmentioning
confidence: 99%